SISTEM AGRIBISNIS USAHA TERNAK AYAM RAS PETELUR (STUDI KASUS CV MULAWARMAN FARM) DI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Pram Andika; Sudarma Widjaya; Adia Nugraha (Lampung University, 2019)
The research aims to determine the supply of production facilities, financial feasibility, and marketing system. This research is a case study at CV Mulawarman Farm in Gadingrejo Subdistrict of Pringsewu Regency. The data was collected in April 2017 and analyzed by qualitative descriptive and finance feasibilities analysis. The result showed that the supply of production facilities at CV Mulawarman Farm did not fully met the expectation because the supply of nipple drinker still occurred delayed for the far distance. The development business at layer chickens farming of CV Mulawarman Farm was profitable enough up to population scaled of 75,000 heads (25 percent larger than the previous population). The egg marketing system of CV Mulawarman Farm distributed to the regular customers that located spreadly in Bandar Lampung, Pringsewu, Tanggamus, and Pesawaran in which the highest percentage of egg marketing distribution was in Bandar Lampung.Key words: agribusiness system, financial feasibility, laying chicken